How Television Invented New Media - Murphy, Sheila C., 1974- (Book collections on Project MUSE., 2011)
How Television Invented New Media adjusts the picture of television culturally while providing a corrective history of new media studies itself. Personal computers, video game systems, even iPods and the Internet built upon and borrowed from television to become viable forms. Sheila C. Murphy analyzes how specific technologies emerge and how representations, from South Park to Dr. Horrible's Sing-Along-Blog, mine the history of television just as they converge with new methods of the making and circulation of images.